Study on the Hydraulic Connectivity between Holocene and Pleistocene Aquifers and the Red River in Hung Yên City Area - Nguyễn, Văn Hoàng (ĐHQGHN, 2015)
The groundwater system in Bac Bo plain in general and in Hung Yên province in particular consists of Holocene aquifers and Pleistocene aquifers. Analysis of the hydraulic connectivity between the Holocene and Pleistocene aquifers plays an important decision on that which conceptual groundwater model is. The latter then decides various analyses regarding the groundwater hydraulic and dynamic regime, the formation of groundwater chemical compounds resulted from different mixing mechanisms, the structure of the groundwater system to be used in numerical simulation etc. This paper focused on the clarification of the hydraulic connectivity between the Holocene aquifer and lower Pleistocene aquifers and their hydraulic connectivity with the main rivers in the area. Comprehensive analysis of the groundwater monitoring water levels with use of the hydraulic parameters of the aquifers, river water level fluctuation had been carried out. The results have shown that there is a negligible hydraulic connectivity between the Holocene and Pleistocene aquifers in H ung Yên province. The fluctuation of groundwater level of lower Pleistocene aquifer has been proved to be dominated by the large river such as the Red river and Duong river by an analytical analysis and finite element modeling. The results of application of finite element modeling had been compared with the analytical results and demonstrated a good match. An important conclusion was made that groundwater resources potential thanks to the Red river for the water needs of the area.